2022
DOI: 10.3389/fimmu.2022.866549
|View full text |Cite
|
Sign up to set email alerts
|

T Helper 2-Associated Immunity in the Pathogenesis of Systemic Lupus Erythematosus

Abstract: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that mainly affects women in their reproductive years. A complex interaction of environmental and genetic factors leads to the disruption of immune tolerance towards self, causing overt immune activation and production of autoantibodies that attack multiple organs. Kidney damage, termed lupus nephritis, is the leading cause of SLE-related morbidity and mortality. Autoantibodies are central to propagating lupus nephritis through forming immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…There is evidence that a negative feedback between Th1-type and Th2-type immune responses regulates normal immune balance. In SLE patients, an influx of Th2 cells inhibits the release of Th1 cells, thus supporting the hypothesis that the immune disorder of “Th2 dominance” is responsible for SLE ( Ko et al, 2022 ).…”
Section: Discussionsupporting
confidence: 69%
“…There is evidence that a negative feedback between Th1-type and Th2-type immune responses regulates normal immune balance. In SLE patients, an influx of Th2 cells inhibits the release of Th1 cells, thus supporting the hypothesis that the immune disorder of “Th2 dominance” is responsible for SLE ( Ko et al, 2022 ).…”
Section: Discussionsupporting
confidence: 69%
“…It has also been explored for treating autoimmune disorders like discoid lupus erythematosus 51. It has also been reported that Th2-associated immunity may play an essential role in a subset patients with SLE,52 echoing our discovery that IL-4 abolishes B ND anergy and contributes to the generation of self-reactive immune responses.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, tumor-specific Th2 cells were also reported to eradicate tumors by triggering an in situ inflammatory immune response [34]. Additionally, the interplay between Th1 and Th2 responses is crucial for maintaining immune balance and preventing pathological conditions [35]. IL-9, mainly produced by Th9 cells, can escalate immune responses by stimulating the production of other pro-inflammatory cytokines (such as IL-4, IL-5 and IL-13), and promote the activity of mast cells, CD8 + T cells, and natural killer (NK) cells.…”
Section: Discussionmentioning
confidence: 99%